An Ethnographic Catalogue in George the Monk’s Chronicle - Chiara Di Serio (Studia Ceranea, 2021)
In Book I of George the Monk’s Chronicle we read a long chapter dedicated to Alexander the Great, which includes an extensive section on his encounter with the Brahmans and the description of their customs. In particular, George the Monk follows the first part of the treatise De Gentibus Indiae et Bragmanibus by Palladius, of which he provides almost verbatim excerpts. Thereafter, we find an ethnographic section devoted to the customs of the Seres, the Bactrians, the Chaldeans, the Gelae, the Britons, and the Amazons. The aim of this study, therefore, is to explore the reception of Greek ethnographic literature in the erudite compilation of George the Monk.